Postoperative urinary symptoms after transobturator tape in normal-weight compared with overweight and obese woman - Hyun Jin Lee; Young Bin Won; Yun Jin Park; Mi Kyung Kong; Sang Wook Bai (Korean Society of Obstetrics and Gynecology, 2018)
ObjectivesTo examine the clinical outcome of obesity in women who underwent the transobturator tape procedure for stress urinary incontinence and to compare postoperative urinary symptoms after transobturator tape surgery between normal-weight women and overweight and obese women.MethodsWe performed a retrospective cohort study of the risk of postoperative urinary symptoms, including recurrence after transobturator tape surgery, in normal-weight women compared with overweight and obese women at our institution from January 2009 through October 2011. We compared the body mass index (BMI) among the four groups. The primary outcome was the occurrence of postoperative urinary symptoms.ResultsThree hundred ten patients who underwent transobturator tape surgery were reviewed. At the 1-year follow-up, 281 women were analyzed: 89 (34%) normal-weight women, 78 (25%) overweight women, 101 (37%) obese 1 women, and 13 (3%) obese 2 women. There was a significant difference in the occurrence of postoperative urinary symptoms. They occurred in 3.4% (n=3) of normal-weight women, 5.1% (n=4) of overweight women, and 12.9% (n=13) of obese 1 women (P=0.038). The most common postoperative urinary symptom was frequent urination (n=14). There was a significant difference in leakage; it occurred in 1.1% (n=1) of normal-weight women, 3.9% (n=3) of overweight women, and 7.9% (n=8) of obese 1 women (P=0.139). Postoperative urinary symptoms were almost four times more likely to occur in obese 1 women than in normal-weight women.ConclusionTransobturator tape surgery seems effective regardless of BMI, but obese women had a higher occurrence of postoperative urinary symptoms than did normal-weight women.